(untitled) (GAIMS Journal of Medical Sciences, 2024)
Background: Dermatoglyphics and obesity both are genetically affected and so there may be a correlation between pattern of fingerprint and body mass index. This study aims at finding such correlation if it persists which can be an effective predictor tool for development of obesity in future. Material and Methods: This study was done on 167 patients coming to general OPD of G K General Hospital, Bhuj. After taking informed consent finger print pattern of all fingers and thumb of both the hands was taken and their BMI was measured. Data was entered in Microsoft excel and statistical analysis was done. Results: In this study the loop pattern was most common in all the 167 participants in both the hands followed by whorl pattern and the least common was arch pattern. The patterns in the individual fingers of the right and left hand were almost similar. In the participants with normal weight, whorl was the most common pattern seen in the thumb compared to thumb of obese and overweight participants who had loop as the common pattern. Conclusions: In our study, no significant correlation was found between any fingerprint pattern and body mass index. This study can be carried out on larger scale with a greater number of participants to establish any correlation in future.